Synthesis of Superconductor Bi1,6Pb0,4Sr2Ca2Cu3O(10+x) for Meissner Test Demonstration Using Solid Reaction Method - Liyana Mardova; Amilia Rasitiani; Dwi Asmi; Leni Rumiyanti; Sigit Dwi Yudanto (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
The research has been done in the field of Field Work Practice to synthesize superconductors Bi1,6Pb0,4Sr2Ca2Cu3O10+x for Meissner test using solid reaction method. The objective of this research is to make superconductor Bi1,6Pb0,4Sr2Ca2Cu3O10 x with solid reaction method and to know the result of superconducting character of Bi1,6Pb0,4Sr2Ca2Cu3O10 +x based on Meissner test. From the results of Meissner test that has been done on this superconductor sample looks super magnet and superconductor repel each other rejects or super magnet drift.Sehingga it can be concluded that the sample has a strong Meissner effect. From the results of Tc test using cryogenic tools obtained Tc Zero temperature of 103.4 K and Tc Onset of 116.67 K. From the data obtained it can be concluded that the sample has reached phase 2223.